Soil-water characteristic curve and permeability function of concrete waste - Sagitaningrum, Fathiyah Hakim; Hamdany, Abdul Halim; Adiguna, Glenn Adriel; Wijaya, Martin; Prakoso, Widjojo Adi; Rahayu, Wiwik; Dewangga, Eriko; Satyanaga, Alfrendo (Frontiers in Built Environment, 2025)
The soil-water characteristic curve (SWCC) and permeability function are critical parameters for understanding the hydraulic behavior of unsaturated soils and are increasingly relevant in evaluating alternative materials for geotechnical and environmental applications. While recycled materials like concrete waste hold promise as substitutes for natural soil, limited research has been conducted to systematically characterize their unsaturated hydraulic properties. In particular, previous studies have largely overlooked the influence of grain size distribution on the SWCC and permeability of concrete waste, resulting in a gap in data necessary for practical application. This study addresses that gap by directly measuring the SWCC and saturated permeability (ks) of concrete waste with varying grain size distributions—a novel approach not widely explored in earlier research. The SWCC was determined using a Tempe cell, and saturated permeability was measured using a constant head test. Results showed that three of the five samples exhibited relatively low ks values, while the remaining two displayed significantly higher permeability. In terms of saturated volumetric water content, In terms of saturated volumetric water content, poorly graded sand demonstrated a greater capacity to retain water, whereas sandy gravel and well-graded sand had much lower water retention, indicating poor drainage. These findings reveal that the hydraulic behavior of concrete waste is highly variable and dependent on its particle size composition and internal structure. By providing new empirical data, this study contributes original insights into the feasibility of using concrete waste as an engineered fill or barrier material in soil-related applications, where understanding unsaturated hydraulic properties is essential for modeling groundwater flow and assessing environmental impact.